2006
DOI: 10.1007/s10532-006-9077-3
|View full text |Cite
|
Sign up to set email alerts
|

Modeling chlorophenols degradation in sequencing batch reactors with instantaneous feed-effect of 2,4-DCP presence on 4-CP degradation kinetics

Abstract: Two instantaneously fed sequencing batch reactors (SBRs), one receiving 4-chlorophenol (4-CP) (SBR4) only and one receiving mixture of 4-CP and 2,4-dichlorophenol (2,4-DCP) (SBRM), were operated with increasing chlorophenols concentrations in the feed. Complete degradation of chlorophenols and high-Chemical oxygen demand (COD) removal efficiencies were observed throughout the reactors operation. Only a fraction of biomass (competent biomass) was thought to be responsible for the degradation of chlorophenols du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Performance of the reactor also decreases with further increase in substrate concentration due to inhibition of microbial growth by substrate concentration itself as reported by Kargi and Eker (2005). The flocs reported by Sahinkaya and Dilek (2007) have a high degradation rate at low concentration, but at high concentration they were also inhibited leading to a decrease in the degradation rate.…”
Section: Co-metabolism and Inhibitionmentioning
confidence: 70%
“…Performance of the reactor also decreases with further increase in substrate concentration due to inhibition of microbial growth by substrate concentration itself as reported by Kargi and Eker (2005). The flocs reported by Sahinkaya and Dilek (2007) have a high degradation rate at low concentration, but at high concentration they were also inhibited leading to a decrease in the degradation rate.…”
Section: Co-metabolism and Inhibitionmentioning
confidence: 70%
“…The substrate degradation efficiency of aerobic granules increases with an increase in substrate concentration up to a certain limit, then decreases (performance of the reactor also decreases) with further increase in substrate concentration, due to inhibition of microbial growth by substrate concentration itself as claimed by Tay et al (2004b) and Khan et al (2011b). It was also reported that microbial flocs have a high degradation rate at low concentration, but at high concentrations they were also rapidly inhibited, leading to a similar decrease in degradation rate (Sahinkaya and Dilek, 2007).…”
Section: Co-metabolism and Inhibitionmentioning
confidence: 95%
“…A very few authors have studied the degradation profile of chlorophenols. Sahinkaya and Dilek (2007) studied the removal rate of 4-chlorophenol (4-CP) and reported the specific degradation rate to be 3.34 mg 4-CP gVSS −1 h −1 (80 mg 4-CP gVSS −1 day −1 ). Wang et al (2000) studied the degradation profile of 2,4-DCP at different concentrations (50, 100, and 200 mg L −1 ) using Bacillus insolitus.…”
Section: Reported That 30mentioning
confidence: 99%